The Influence of Business Strategy and Environmental Uncertainty to The Characteristics Management Accounting Information System - Adi Praptika Jaya; Siti Ira Octaviany; Gun Gunawan Rachman (SEAN Institute, 2024)
The characteristics of management accounting information systems can be influenced by Business Strategy and Environmental Uncertainty. Business Strategy in the Company has been implemented and is running well. In addition, the ability to predict the level of environmental uncertainty owned by employees of PT Multi Garmen Jaya is good. This research was conducted, aims to determine how much influence business strategy and environmental uncertainty have on the characteristics of management accounting information systems at PT Multi Garmen Jaya. The methods used in this research are descriptive and verification methods. The population taken for this study were employees of PT Multi Garmen Jaya. Sampling was done by probability sampling with simple random sampling technique with a sample of 37 respondents. The types of data used in this study are primary and secondary data. Data processing techniques using statistical test modelling with the Structural Equation Modelling - Partial Least Square (SEM-PLS) version 3.0 program. The results of this study indicate that: 1) business strategy affects the characteristics of management accounting information systems. 2) environmental uncertainty affects the characteristics of management accounting information systems.